Teleconference Use among Office Workers: An Interorganizational Comparison of an Extended Theory of Planned Behavior Model - Siu Hing Lo; Gerard J.P. van Breukelen; Gjalt-Jorn Y. Peters; Gerjo Kok (Administrative Sciences, 2014)
From a corporate social responsibility perspective, there are many reasons to promote teleconference use as an alternative to business travel. The present study examines psychosocial and organizational factors relevant to teleconference use. We tested an extended Theory of Planned Behavior model of teleconference use among office workers of four organizations. Results indicate that intention was the strongest direct predictor of teleconference use. Habit and perceived norm, in turn, were the strongest predictors of intention to use teleconference. In contrast, attitude was only weakly predictive and perceived control not predictive at all of intention to use teleconference. We also examined how this model was influenced by the organizational context by comparing organizations from two different regions, and organizations from the private vs. the public sector. Most teleconference-related beliefs differed between regions and organizational sectors. The relevance of specific attitudinal and normative beliefs to the overall attitude and perceived norm also differed between organizational sectors. Implications for practice and future research are discussed.